Tahap tingkah laku buli di kalangan pelajar di sekolah menengah Daerah Semporna - Rozanah, Madsarapi (2011)
This research is to identify level of bully in Semporna district secondary schools. This research is also to identify types, frequency and causes of bully, among secondary school students as well as bully victims characteristics. The total of 120 form 4 students from 4 different schools in Semporna district were chosen as samples. The instrument used in this research is a set of questionares of School Bullying Index which has a value of realibility of a =0.87. Desciptive statistic comparises frequency, percentage, min and standard defiency were used to analyse the level of bully cases in school. Statistic of inference, the t-test analysis, is use to analyse the difference of bully based on gender aspects. Overall, the level of bully cases in secondary schools is low. The research had proven that there is no difference in bully neither among boys or girls